ANALYSIS OF TAX COMPLIANCE BEHAVIOR: AN EXPERIMENTAL STUDY ON THE INFLUENCE OF MORAL MESSAGES AND THREATS OF SANCTIONS ON VOLUNTARY TAX COMPLIANCE - Irfan Wahyudi; Farida Aryani; Wiljan Atfentia Kotngoran; Nelly Ervina; Riny (ITB AAS Indonesia Surakarta, 2026)
Voluntary tax compliance is a key pillar in maintaining a country's fiscal sustainability, yet tax authorities often face a dilemma between using a persuasive or coercive approach. This study aims to analyze taxpayer compliance behavior through an experimental study, focusing on the influence of moral messages and the threat of sanctions on voluntary compliance levels. Using a 2x2 between-subjects laboratory experimental design, participants were presented with tax scenarios that manipulated the presence of moral messages (non-moral vs. moral) and the level of sanction threat (high vs. low). Data analysis results indicate that moral messages significantly increase voluntary compliance because they activate individuals' internal norms (Khlif & Achek, 2015). On the other hand, a high threat of sanctions has been shown to be effective in increasing compliance immediately, but risks eroding taxpayers' intrinsic motivation in the long run (Alm & Torgler, 2011). Interestingly, the interaction between the two variables indicates that delivering moral messages combined with credible but moderate sanctions produces the most stable compliance levels. These findings imply the importance of tax authorities shifting their paradigm from merely rigid law enforcement to communication strategies that address the psychological and moral aspects of taxpayers.